A Kinetic Study of Oxidation of Aliphatic Ketone with N-Bromobenzamide in Acidic Medium - P. Dubey, R.; Kumari, Geeta; K. Solanki, S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of ethyl methyl ketone by N-bromobenzamide (NBB) in aquoacetic acid media has been done. The reaction has a zero order dependency on [NBB] and a first order dependency with respect to substrate [ethyl methyl ketone]. The reaction is catalysing by H+. The effect of ionic strength, mercuric acetate and product [benzamide] variations has been studied. Various thermodynamic parameters have been computed and a probable reaction mechanism consistent with the kinetic results has been suggested.